1986
DOI: 10.1021/bi00366a002
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of phosphodiesterase activation is greatly reduced by rhodopsin phosphorylation

Abstract: In the vertebrate rod outer segment (ROS), the light-dependent activation of a GTP-binding protein (G-protein) and phosphodiesterase (PDE) is quenched by a process that requires ATP [Liebman, P.A., & Pugh, E.N. (1979) Vision Res. 19, 375-380]. The ATP-dependent quenching mechanism apparently requires the phosphorylation of photoactivated rhodopsin (Rho*); however, a 48-kilodalton protein (48K protein) has also been proposed to participate in the inactivation process. Purified species of phosphorylated rhodopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 26 publications
(31 reference statements)
1
60
0
Order By: Relevance
“…These results indicate that the nonphosphorylated P␥ retains its complex with GTP␥S/T␣ in the homogenate; however, after the P␥ is phosphorylated by Cdk5, the phosphorylated P␥ cannot keep its complex with GTP␥S/T␣ and inhibits effectively GTP␥S/T␣-activated PDE. We note that the effect of P␥ phosphorylation on the time course of light/GTP␥S-dependent PDE activation could not be measured by adding ATP to the homogenate, because rhodopsin in the homogenate is also phosphorylated, and the phosphorylated rhodopsin may affect the light/GTP␥S-activated PDE activity (33,34). We also note that 300 nM amounts of these P␥s, free or complexed with GDP/T␣ or GTP␥S/T␣, were used in these experiments, because by using the high concentration of P␥, we tried to clearly show that even a small portion of nonphosphorylated P␥ was not released from its complexes with GDP/T␣ or GTP␥S/T␣.…”
Section: Fig 4 Effect Of Cdk Inhibitors On P␥ Phosphorylation In VImentioning
confidence: 99%
“…These results indicate that the nonphosphorylated P␥ retains its complex with GTP␥S/T␣ in the homogenate; however, after the P␥ is phosphorylated by Cdk5, the phosphorylated P␥ cannot keep its complex with GTP␥S/T␣ and inhibits effectively GTP␥S/T␣-activated PDE. We note that the effect of P␥ phosphorylation on the time course of light/GTP␥S-dependent PDE activation could not be measured by adding ATP to the homogenate, because rhodopsin in the homogenate is also phosphorylated, and the phosphorylated rhodopsin may affect the light/GTP␥S-activated PDE activity (33,34). We also note that 300 nM amounts of these P␥s, free or complexed with GDP/T␣ or GTP␥S/T␣, were used in these experiments, because by using the high concentration of P␥, we tried to clearly show that even a small portion of nonphosphorylated P␥ was not released from its complexes with GDP/T␣ or GTP␥S/T␣.…”
Section: Fig 4 Effect Of Cdk Inhibitors On P␥ Phosphorylation In VImentioning
confidence: 99%
“…This is the first study to date to correlate the reduced ability of the phosphorylated receptor to both bind and activate the G protein. Although it has been proposed that phosphorylation of rhodopsin reduces its binding affinity for transducin (18), evidence to support this is lacking. Multiple studies have demonstrated that the rhodopsin domains most critical for transducin binding are the second and third cytoplasmic loops (33)(34)(35)(36).…”
Section: Fig 2 Arrestin Binding To Rhodopsin and Phosphorhodopsinmentioning
confidence: 99%
“…Although several studies have demonstrated a modest to potent functional effect of receptor phosphorylation on G protein activation, it is not known whether this effect is due to attenuated G protein binding to the receptor or subsequent G protein activation. Phosphorylated rhodopsin was demonstrated to have a significantly lower light-induced phosphodiesterase activating capacity than nonphosphorylated rhodopsin (4,18), and it was subsequently proposed that rhodopsin phosphorylation reduces the binding affinity for transducin (18). ␤ARK phosphorylation of the ␤ 2 AR resulted in a modest functional inhibition of ␤ 2 AR-stimulated G o GTPase activity (12,15), and phosphorylation of the m2 muscarinic acetylcholine receptor by ␤ARK modestly reduced its capacity to stimulate GTP␥S binding to G o (19).…”
mentioning
confidence: 99%
“…At the first step, this is due to rhodopsin phosphorylation that causes a considerable decrease in the rate of T activation [4][5][6][7][8]. The phosphorylation effect can be apparently enhanced as a result of the binding of an ROS cytoplasmic 48 kDa protein to phosphorylated rhodopsin [9].…”
Section: Introductionmentioning
confidence: 99%